It is not the cow, it is the how - Louhaichi, Mounir (Krishi Publisher, 2024)
The research was presented at the International Conference on Feeding the Future through Sustainable Eco-friendly Innovations in Rangeland, Forages, and Animal Sciences in Bangalore, India: Worldwide, rangelands encompass over 50% of the Earth's land area. For millennia, pastoralism has served as an adaptive strategy on these lands, enabling pastoral communities to navigate fluctuating and unpredictable climates. This ancient practice remains the most effective approach to maintaining the equilibrium of rangeland ecosystems, benefiting both humanity and the natural world. The aim of this abstract is to highlight the benefits of opportunistic grazing. The study identified primary challenges and provided a roadmap for restoring degraded silvopastoral systems in a semi-arid region. It explored a state-owned silvopastoral site in a semi-arid Tunisia region, highlighting challenges such as the lack of effective collaboration among departments and stakeholders and the detrimental effect of prolonged livestock exclusion on the ecosystem. Interventions involved erosion mitigation, afforestation with native species, and promoting multi-stakeholder engagement and supportive policies. The study underscores the importance of collaborative strategies in revitalizing degraded ecosystems.